DATA-DRIVEN DECISION MODELING AND SUSTAINABLE COMPETITIVENESS IN THAI SMES IN WELLNESS AND BEAUTY SECTOR: AN OPERATIONAL RESEARCH FRAMEWORK - Jaruwan Lim; Sumaman Pankham (Operational Research in Engineering Sciences: Theory and Applications)
The study examines how sustainable competitive advantage can be enhanced using strategic information practices and digital communication technologies in the Thai digital wellness and beauty industry. By analysing the behaviour of SMEs in dealing with digital information, patient use of social media platforms, and the implementation of communication technologies, the research investigates how these practices contribute to developing resilience, innovation, and sustained competitiveness in a data-driven market environment. A mixed-methods design was utilized. Expert interviews were conducted as the initial step, following the Rough Set e-Delphi methodology, with 21 experts focusing on key constructs related to the information-centric nature, including digital content strategy, social media involvement, and knowledge-based customer relationship management. The second phase involved a quantitative study of 652 SME entrepreneurs, utilizing Structural Equation Modeling (SEM) to examine causal relationships. Key findings reveal that social media significantly enhances customer relationship management, while market orientation and entrepreneurial orientation positively influence innovation capability. Innovation capability and brand trust significantly increase the sustainable competitive advantage, while customer relationship management has a significant negative impact on sustainable competitive advantage, which suggests the need for more personalized and value-aligned CRM practices. Mediation analysis further indicates that customer relationship management fully mediates the effect of social media on sustainable competitive advantage, and innovation capability fully mediates the market orientation and sustainable competitive advantage relationship. The study findings can theoretically contribute to the literature in the field of strategic management by combining resource-based, market-based, and dynamic capability perspectives to explain them in the case of digital SMEs. In practice, the confirmed model can provide a set of recommendations to entrepreneurs, policymakers, and business strategists to improve SMEs' resistance to change and sustainability.